Development of a TaqMan® Allelic Discrimination qPCR Assay for Rapid Detection of Equine CXCL16 Allelic Variants Associated With the Establishment of Long-Term Equine Arteritis Virus Carrier State in Stallions - Thieulent, Come J.; Carossino, Mariano; Balasuriya, Udeni B. R.; Graves, Kathryn; Bailey, Ernest; Eberth, John; Canisso, Igor F.; Andrews, Frank M.; Keowen, Michael L.; Go, Yun Young (Frontiers in Genetics, 2022)
Equine arteritis virus (EAV) is the causative agent of equine viral arteritis (EVA), a respiratory, systemic, and reproductive disease of equids. Following natural infection, up to 70% of the infected stallions can remain persistently infected over one year (long-term persistent infection [LTPI]) and shed EAV in their semen. Thus, the LTP-infected stallions play a pivotal role in maintaining and perpetuating EAV in the equine population. Previous studies identified equine C-X-C motif chemokine ligand 16 (CXCL16) as a critical host cell factor determining LTPI in the stallion's reproductive tract. Two alleles (CXCL16S and CXCL16r) were identified in the equine population and correlated with the susceptibility or resistance of a CD3+ T cell subpopulation in peripheral blood to in vitro EAV infection, respectively. Interestingly, CXCL16S has been linked to the establishment of LTPI in stallions, and thus, genotyping stallions based on CXCL16S/r would allow identification of those at the highest risk of establishing LTPI. Thus, we developed a TaqMan® allelic discrimination assay for the genotyping of the equine CXCL16 gene based on the identification of single nucleotide polymorphism in position 1073 based on the NCBI gene ID: 100061442 (or position 527 based on Ensembl: ENSECAG00000018406.2) located in exon 2. One hundred and sixty horses from four breeds were screened for the CD3+ T cell susceptibility phenotype to EAV infection by flow cytometry and subsequently sequenced to determine CXCL16 allelic composition. Genotyping by Sanger sequencing determined that all horses with the resistant CD3+ T cell phenotype were homozygous for CXCL16r while horses with the susceptible CD3+ T cell phenotype carried at least one CXCL16S allele or homozygous for CXCL16S. In addition, genotypification with the TaqMan® allelic discrimination assay showed perfect agreement with Sanger sequencing and flow cytometric analysis. In conclusion, the new TaqMan® allelic discrimination genotyping assay can be used to screen prepubertal colts for the presence of the CXCL16 genotype. It is highly recommended that colts that carry the susceptible genotype (CXCL16S/S or CXCL16S/r) are vaccinated against EAV after six months of age to prevent the establishment of LTPI carriers following possible natural infection with EAV.